2011
DOI: 10.1080/09575146.2011.610299
|View full text |Cite
|
Sign up to set email alerts
|

Problematic placement: pathways pre-service teachers’ perspectives on their infant/toddler placement

Abstract: The inclusion of an infant/toddler placement in a 'pathways' early childhood teaching degree, where students already have qualifications and experience in working with young children, can be problematic. This pilot study investigated student teachers' views on their infant/toddler (birth-to-two-years) placement. Sixty-six students completing their early childhood education degree at an Australian university responded to a survey seeking their perspectives on the effectiveness of the placement in developing tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
1
15
0
5
Order By: Relevance
“…An important aspect of the Childcare Act (2007) is that it specifically states its focus on care prior to school age, explicitly excluding children aged 3 years and above enrolled in educational programs on school sites. This resonates with some long held views that a teacher's role in early childhood education should be confined to preschool programs (Rouse, Morrissey, & Rahimi, 2012 Act (2012a) included the procedure for being audited against the National Quality Standard (COAG, 2009b) and the responsibility of the regulatory body, the Australian Children's Education and Care Quality Authority (ACECQA), in governing this process.…”
Section: The Early Yearsmentioning
confidence: 93%
See 1 more Smart Citation
“…An important aspect of the Childcare Act (2007) is that it specifically states its focus on care prior to school age, explicitly excluding children aged 3 years and above enrolled in educational programs on school sites. This resonates with some long held views that a teacher's role in early childhood education should be confined to preschool programs (Rouse, Morrissey, & Rahimi, 2012 Act (2012a) included the procedure for being audited against the National Quality Standard (COAG, 2009b) and the responsibility of the regulatory body, the Australian Children's Education and Care Quality Authority (ACECQA), in governing this process.…”
Section: The Early Yearsmentioning
confidence: 93%
“…However, a recent study examining teachers' perceptions of their abilities to be educational leaders in Victorian childcare settings found that teachers reported feeling that their qualification did not earn them an automatic right to suggest or implement change, especially as they often saw the work they did as fundamentally similar to that of the other staff (Grarock & Morrissey, 2013). Rouse, Morrissey and Rahimi (2012) argue that the policy for all childcare settings to employ a degree-qualified teacher by 2014 is widening the education and care divide in early childhood settings with the role of the diploma-qualified early childhood practitioner now viewed as less worthy with lower status than that of the degree qualified teacher.…”
Section: The Early Yearsmentioning
confidence: 99%
“…Previous Australian research suggests that qualified teachers in childcare centers end up working with older children; while diploma and certificate qualified educators (or sometimes unqualified staff) work with the younger children (Rouse, Morrissey & Rahimi, 2012). Therefore, younger children tend to receive little time with a qualified early childhood teacher.…”
Section: Literaturementioning
confidence: 99%
“…Australian Government requirements also demand that qualified teachers work with older aged children as part of a universal access agreement that allows all children, in the year before schooling, access to an early childhood teacher (Rouse, Morrissey, & Rahimi, 2012). Previous Australian research suggests that qualified teachers in childcare centers end up working with older children; while diploma and certificate qualified educators (or sometimes unqualified staff) work with the younger children (Rouse, Morrissey & Rahimi, 2012).…”
Section: Literaturementioning
confidence: 99%
“…An underlying expectation with the policy reform has been that degree-qualified teachers will work with children under three years of age through a leadership and mentoring role, however government requirements demand that qualified teachers work with pre-school aged children (Rouse, Morrissey & Rahimi, 2012). Other research reports that qualified teachers in childcare centres end up working with older children, while diploma and certificate qualified educators (or sometimes unqualified staff) are more likely to work with the younger children (Ireland, 2006;Norris, 2010;Rouse, 2008).…”
Section: The Australian Early Childhood Contextmentioning
confidence: 99%